Long-term Quantitative and Qualitative Assessment of the Corneal Endothelium after Anterior Radial Keratotomy - M. M. Bikbov; A. A. Bikbulatova; V. K. Surkova; N. V. Pasikova (Oftalʹmologiâ)
Purpose. To determine the long-term status of the corneal endothelium after anterior radial keratotomy. Patients and methods. The main group consisted of 69 patients (104 eyes) who underwent radial or radial-tangential keratotomy to correct myopia and myopic astigmatism an average of 23,1±2,8 years ago (range 16 to 30 years). The average age of patients was 53,8±5,7 years (range 39 to 65 years). The number of keratotomy scars ranged from 4 to 14. Repeated keratotomy was performed on 8 eyes. The control group consisted of 56 patients (110 eyes) aged from 39 to 64 years(average 54,2±4,3 years) with refractive-axial myopia from medium to high stage, whom potentially could be done anterior keratotomy in the 90th of the last century. Patients with concomitant pathology and ocular trauma that could lead to loss ofendothelial cells were excluded from both groups. Corneal endothelium cell densit y, polimegatizm, pleomorphism in addition to standard eye examination were performed to all patients with the help of contactless endothelial microscope «EM-3000» company Tomey (Japan). Results. In the control group endothelial cell densit y averaged 2734,8±121,2 cells /mm2, in the main group — 2134,2±299,1 cells/mm2 (p <0,05), in group after repeated keratotomy — 1679,9±327,3 cells/mm2 (p≤0,0001). Endothelial cell densit y in patients with biomicroscopic signs of intraoperative perforation of the cornea — an average of 2012,2±245,7 cells/mm2, without signs of perforation — 2378,4±242,9 cells/mm2. In the main group the coefficient of variation averaged 0,47±0,06, in the control group — 0,28±0,03 (p<0,05). In the main group percentage of hexagonal cells averaged 37,9±9,4, in the control group — 69,2±6,3 (p<0,05). Conclusions. Anterior keratotomy leads to a significant reduction in the endothelial cell densit y, increasing the size and coefficient of variation, decreasing percentageof hexagonal cells in the long-term. Endothelial cell densit y is significantly lower in patients after repeated keratotomy and in patients with the signs of corneal intraoperative perforations.